Identification of antibiotic-resistant Escherichia coli isolated from a municipal wastewater treatment plant. (December 2016) - Zanotto, Carlo; Bissa, Massimiliano; Illiano, Elena; Mezzanotte, Valeria; Marazzi, Francesca; Turolla, Andrea; Antonelli, Manuela; De Giuli Morghen, Carlo; Radaelli, Antonia
Abstract: The emergence and diffusion of antibiotic-resistant bacteria has been a major public health problem for many years now. In this study, antibiotic-resistance of coliforms and Escherichia coli were investigated after their isolation from samples collected in a municipal wastewater treatment plant in the Milan area (Italy) along different points of the treatment sequence: inflow to biological treatment; outflow from biological treatment following rapid sand filtration; and outflow from peracetic acid disinfection. The presence of E. coli that showed resistance to ampicillin (AMP) and chloramphenicol (CAF), used as representative antibiotics for the efficacy against Gram-positive and Gram-negative bacteria, was evaluated. After determining E. coli survival using increasing AMP and CAF concentrations, specific single-resistant (AMP R or CAF R ) and double-resistant (AMP R /CAF R ) strains were identified among E. coli colonies, through amplification of the β-lactamase Tem-1 ( bla ) and acetyl-transferase catA1 ( cat ) gene sequences. While a limited number of CAF R bacteria was observed, most AMP R colonies showed the specific resistance genes to both antibiotics, which was mainly due to the presence of the bla gene sequence. The peracetic acid, used as disinfection agent, showed to be very effective in reducing bacteria at the negligible levels of less than 10 CFU/100 mL, compatible with those admitted for the irrigation use of treated waters. Graphical abstract: Highlights: AMP R Escherichia coli colonies are prevalent among AMP R coliforms. AMP R and CAF R E. coli show a 2-log decrease after the biological treatment. Bla + E. coli percentage increases after the biological treatment and filtration. AMP R /CAF R double-resistant E. coli colonies are mostly bla + .